OTP system with third party trusted authority as a mediator (International Journal of Engineering and Computer Science, 2017)
One Time Password is one of the preferable security techniques to do online transaction. If the security level is compared, it shows the need of improvement in its transaction methods and medium. In this paper, two authorities are considered viz. bank domain itself and third party as a trusted authority. Third party authority will have its own secrete key based on its own considered attributes. This key will be combined with user attribute key to form encrypted key. This key will be stored in temp database till session time is available. Here the two new concepts are added as to use third party secrete key and storing this key into temp database for predefined session time only. After these stages only main database can be accessed. It will increase the security level to make secure online transaction.